Exome sequencing data reanalysis of 200 hypertrophic cardiomyopathy patients: the HYPERGEN French cohort 5 years after the initial analysis - Jaouadi, Hager; Morel, Victor; Martel, Helene; Lindenbaum, Pierre; Lamy de la Chapelle, Lorcan; Herbane, Marine; Lucas, Claire; Magdinier, Frédérique; Habib, Gilbert; Schott, Jean-Jacques; Zaffran, Stéphane; Nguyen, Karine (Frontiers in Medicine, 2024)
Background: Approximately half of hypertrophic cardiomyopathy (HCM) patients lack a precise genetic diagnosis. The likelihood of identifying clinically relevant variants increased over time.Methods: Herein, we conducted a gene-centric reanalysis of exome data of 200 HCM cases 5 years after the initial analysis. In this reanalysis, priority was given to genes with a matched HCM entry in OMIM database and recently emerging HCM-associated genes gathered using text mining-based literature review. Further classification of the identified genes and variants was performed using ClinGen resource and ACMG guidelines to assess the robustness of gene-disease association and the clinical actionability of the prioritized variants.Results: As expected, the majority of patients carried variants in MYBPC3 and MYH7 genes 26% (n=51) and 8% (n=16) respectively, in accordance with the initial analysis. The vast majority of pathogenic and likely pathogenic variants were found in MYBPC3 (22 out of 40 variants) and MYH7 (8 out of 16 variants) genes. Three genes, not included in the initial analysis, were identified: SVIL, FHOD3, and TRIM63. Considering only patients with unique variants in the last three genes, there was a 9% enhancement in variant identification.Importantly, SVIL variants carriers presented apical and septal HCM, aortopathies, and severe scoliosis for one patient. Ten patients (5%) carried variants in FHOD3 gene, six of them in hotspot regions (Exons 12 and 15). We identified seven variants within the TRIM63 gene in 12 patients (6%). Homozygous variants were detected in 2.5% of the cohort in MYBPC3 (n=1), MYL3 (n=1), and TRIM63 (n=3) genes.No variants were found in the ACTC1, TPM1, and TNNI3 genes in the HYPERGEN cohort. Thus, variants were identified in five out of the eight HCM core genes with high prevalence in young patients. We identified variants in three recent HCMassociated genes (SVIL, FHOD3, and TRIM63) in 35 patients, with 18 patients carrying unique variants (9%). Our results further emphasize the usefulness of exome data reanalysis particularly in genotype-negative patients.